Development of Non-Invasive Ultrasonic Measuring System for Monitoring Multiphase Flow in Liquid Media within Composite Pipeline - Mohd Fadzli Abd Shaib; Ruzairi Abd Rahim; S.Z.M. Muji (Institute of Advanced Engineering and Science, 2017)
Process of conveying liquid substance via the pipeline is the most common practice of transferring the liquid from one point to another point. Composite pipeline is becoming an option for liquid conveying purposed (instead of PVC, acrylic or metal) for its durability, longer lifetime and non-corrosive material in comparison with current pipeline. In order to ensure, the conveying process has a smooth flow rate without particle or bubble disturbance that could hinder good process flow, non-invasive monitoring system is always required. The ultrasonic measuring system is one of the monitoring options that could be applied. With proper designed for transmitting and conditioning circuitry, 300 kHz ultrasonic frequencies are found as the optimal frequency needed to penetrate across the composite pipeline with full of liquid. The ultrasonic sensor response is being successfully differentiated between full flow (no material blockage) and with bulk material blockage (dry and wet sand).